Diagnostic accuracy of ultrasound in detecting the severity of abnormally invasive placentation: a systematic review and meta‐analysis. (28th November 2017) - Pagani, Giorgio; Cali, Giuseppe; Acharya, Ganesh; Trisch, Ilan‐Timor; Palacios‐Jaraquemada, Jose; Familiari, Alessandra; Buca, Danilo; Manzoli, Lamberto; Flacco, Maria E.; Fanfani, Francesco; Liberati, Marco; Scambia, Giovanni; et al.
Abstract: Introduction: Our objective was to elucidate the overall diagnostic accuracy of ultrasound in detecting the severity of abnormally invasive placentation (AIP). Material and methods: Medline, Embase, CINAHL and The Cochrane databases were searched. The ultrasound signs explored were: loss of hypoechoic (clear) zone in the placental–uterine interface, placental lacunae, bladder wall interruption, myometrial thinning, focal exophitic mass, placental lacunar flow, subplacental vascularity, and uterovesical hypervascularity. Results: Twenty studies (3209 pregnancies) were included. Ultrasound had an overall good diagnostic accuracy in identifying the depth of placental invasion with sensitivities of 90.6%, 93.0%, 89.5%, and 81.2% for placenta accreta, increta, accreta/increta, and percreta, respectively; the corresponding specificities were 97.1%, 98.4%, 94.7%, and 98.9%. Placental lacunae had sensitivities of 74.8%, 88.6%, and 76.3% for the detection of placenta accreta, increta, and percreta, respectively. Sensitivity and specificity of loss of the clear zone in identifying placenta accreta were 74.9% and 92.0%, whereas the corresponding figures for placenta increta and percreta were 91.6% and 76.9%, and 88.1% and 71.1%. Lacunar flow had sensitivities of 81.2%, 84.3%, and 45.2% for the detection of placenta accreta, increta, and percreta respectively; the corresponding figures for specificity were 84.0%, 79.7%, and 75.3%. Sensitivity of uterovesical hypervascularity was low for the detection of placenta accreta (12.3%) but high for placenta increta (94.4%) and percreta (86.2%); the corresponding figures for specificity were 90.8%, 88.0% and 88.2%, respectively. Conclusions: Ultrasound has an overall good diagnostic accuracy in recognizing the depth and the topography of placental invasion.